Semiblind channel estimation and equalization for MIMO space-time coded OFDM - Yonghong Zeng; Lam, W.H.; Tung Sang Ng (IEEE transactions on circuits and systems. I, Regular papers, 2006)
Based on the special features of space-time coding (STC) and orthogonal frequency-division multiplexing (OFDM), it is mathematically proved that all channel responses of a multiple-input-multiple-output STC-OFDM system can be identified blindly subject to two ambiguity matrices with a subspace-based method. A method is then presented to resolve the two ambiguity matrices by using few pilot symbols. With the estimated channels, a frequency domain approach is presented to recover the transmitted symbols. The presented semiblind algorithms are valid even if the channel transfer functions are not coprime and do not require precise channel order information (only an upper bound for the orders is required).